Site investigation / Meor Muhammad Fairiel Meor Sharul Halizan - Meor Sharul Halizan, Meor Muhammad Fairiel (Universiti Teknologi MARA, Perak, 2022)
To maintain integrity and honesty of work by contractor and to ensure whether a proposed construction projects is safe to proceed to ensure safety and to understand the site location or condition and equipment needed for the project, a testing before construction work begins is vital. Therefore, this report will discuss about the pre-construction testing that is required before begin the construction work. Many new knowledge was discover while undergoing practical training with the company in many ways such as questionnaires interview, observation, document reviews and hands on training. The objective of the report is to to identify method of laboratory testing for site investigation, to identify on-site testing for site investigation and to identify the problem and solution at site regarding site investigation. The laboratory testing are more to soil investigation work in which purpose to investigate the condition of the soil at the site location. Meanwhile, on site testing are testing that needs to be carry out on site, as the information can only be gain as the conducted on site. Problem and solution at site regarding site investigation discussed about the the issue that encountered on site while conducting the test. Testing before starting construction work is a fundamental step, which held prior to any construction activity on site. The obtained data will assist in designing phase therefore a good quality, economic and safe structure can be built accordingly to the what site location needed.